Amino acid transport in plants - Fischer, W.N.; André, B.; Rentsch, D.; Krolkiewicz, S.; Tegeder, M.; Breitkreuz, K.; Frommer, W.B.
Amino acids are transported between different organs through both xylem and phloem. This redistribution of nitrogen and carbon requires the activity of amino acid transporters in the plasma membrane. In addition, amino acids can be taken up directly by the roots. Amino acid transport has been well characterized in the yeast Saccharomyces cerevisiae, and functional complementation has served as an excellent tool for identifying and characterizing amino acid transporters from plants. The transporters from yeast and plants are related and can be grouped into two large superfamilies. Based on substrate specificity and affinity, as well as expression patterns in plants, different functions have been assigned to some of the individual transporters. Plant mutants for amino acid transporter genes are now being used to study the physiological functions of many of the cloned genes.